Linguistic Poetics of Units Formed on the Basis of the Cosmonym Moon in the Poetry of Usman Nasir - Jurabek Yuldashev (Researchparks Publishing, 2022)
This article provides information on the use of the cosmonym moon in various forms, used in the poetry of Usman Nasir and carrying a poetic meaning.